The Effectiveness Of The Prevention Program By The BNNK Sleman In The Context of an Anti-Drug Campaign - Yoga Surya Wijaya; Angga Intueri Mahendra P. (PT Mattawang Mediatama Solution, 2023)
The anti-drug campaign is still being carried out by the government to reduce the number of drug abuse. Through the BNNK Sleman, areas in Sleman Regency continue to make efforts to prevent and assist the community. The activities carried out are a form of anti-drug campaign efforts. There are still cases of drug abuse that have even begun to target teenagers, which is a problem that needs to be addressed immediately. Researchers will see how the effectiveness of the prevention program carried out is related to the anti-drug campaign in Sleman Regency. This research uses a descriptive method with a qualitative approach. The results of this study are that the BNNK Sleman has carried out several prevention activities, namely the Shining Village Program, Family Resilience, Youth Resilience, KIE, Counseling, and utilization through social media. Activities that have been carried out by the BNNK Sleman through the P2M sub-sector related to prevention within the framework of the anti-drug campaign have been quite effective and right on target. Demonstrated by the understanding and application of the material that has been obtained during the activity. In addition, there has been awareness from the community regarding the anti-drug campaign as indicated by the many requests from the public for the BNNK Sleman to provide assistance as well as outreach and education to the community.